2016
DOI: 10.1136/neurintsurg-2016-012715.rep
|View full text |Cite
|
Sign up to set email alerts
|

Republished: Remote multifocal bleeding points producing a Sylvian subpial hematoma during endovascular coiling of an acutely ruptured cerebral aneurysm

Abstract: Subpial hematoma is a rare type of intracranial hemorrhage with a poor prognosis. A new mechanism to explain subpial Sylvian hematoma formation in acute post-aneurysmal subarachnoid hemorrhage (SAH) was observed during coiling of a posterior communicating artery aneurysm. Multiple small bleeding points from pial branches of the left middle cerebral artery, which were remote from the ruptured aneurysm, were observed on conventional angiography. This bleeding led to the formation of a large expanding subpial Syl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In addition, van Donkelaar et al [ 25 ] reported that the amount of blood acted as a surrogate marker of the defect size and stability of the ruptured aneurysm wall, showing a high correlation with the occurrence of rebleeding within 24 hours when the modified Fisher grade was 3 to 4 (aHR 4.7, 95% CI [2.1-0.6]). In addition, Hilditch et al [ 10 ] reported a case of rupture of small pial branches of sylvian middle cerebral artery by expansion of sylvian fissure hematoma after acute post-aSAH, causing remote multifocal bleeding, resulting in the formation of hematoma in the sylvian subpial space. As a result, it was argued that there is a relationship between hematoma amount and remote hemorrhage, as the greater the amount of SAH caused by ruptured aneurysm, the greater the expanding effect of sylvian fissure and the likelihood of the occurrence of remote subpial bleeding will increase.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, van Donkelaar et al [ 25 ] reported that the amount of blood acted as a surrogate marker of the defect size and stability of the ruptured aneurysm wall, showing a high correlation with the occurrence of rebleeding within 24 hours when the modified Fisher grade was 3 to 4 (aHR 4.7, 95% CI [2.1-0.6]). In addition, Hilditch et al [ 10 ] reported a case of rupture of small pial branches of sylvian middle cerebral artery by expansion of sylvian fissure hematoma after acute post-aSAH, causing remote multifocal bleeding, resulting in the formation of hematoma in the sylvian subpial space. As a result, it was argued that there is a relationship between hematoma amount and remote hemorrhage, as the greater the amount of SAH caused by ruptured aneurysm, the greater the expanding effect of sylvian fissure and the likelihood of the occurrence of remote subpial bleeding will increase.…”
Section: Discussionmentioning
confidence: 99%